Cellulose-containing rubber composition

JP2025029247APending Publication Date: 2025-03-06THE YOKOHAMA RUBBER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023133763
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-03-06

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、発熱し難く、且つ耐摩耗性および耐チッピング性がいずれも優れたセルロース含有ゴム組成物を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029247000001_ABST
    Figure 2025029247000001_ABST
Patent Text Reader

Abstract

To provide a cellulose-containing rubber composition which hardly generates heat and is excellent in both wear resistance and chipping resistance.SOLUTION: The rubber composition is obtained by blending a diene rubber, an inorganic filler, a cellulose-containing master batch, and a mixture of a fatty acid and a resin acid. The cellulose-containing master batch contains a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid. The rubber composition contains 30-100 pts.mass of the inorganic filler, 0.5-10 pts.mass of the cellulose, and 0.2-8 pts.mass of the total of the mixtures of the fatty acids and the resin acids based on 100 pts.mass of the total of the diene rubbers.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cellulose-containing rubber composition and a tire using the cellulose-containing rubber composition. [Background technology]

[0002] Rubber compositions for tires and the like are required to have excellent properties such as elastic modulus (elongation), hardness (hardness), etc. To improve such properties, a technique is known in which inorganic fillers such as carbon black and silica are blended into the rubber composition.

[0003] Furthermore, from the viewpoint of efficient use of resources and weight reduction, a technique of compounding cellulose (including nanocellulose, which is an ultrafine fiber of cellulose) as a filler in a rubber composition has been developed. For example, Patent Document 1 discloses a rubber composition that contains modified cellulose nanofibers and a rubber component and has sufficient reinforcing properties even when a large strain is applied. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-095611 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the production of masterbatches (rubber masterbatches), etc., cellulose does not have a high affinity with rubber components, so there is a problem that it is difficult to disperse it uniformly. In particular, nanocellulose has a property that it easily aggregates and aggregates during processes such as solidification and drying to remove moisture during the production of masterbatches, so even in modified nanocellulose such as that in Patent Document 1, it is quite difficult to keep the nanocellulose uniformly dispersed and defibrated to the nano level. And if a masterbatch in which the cellulose is not uniformly dispersed is used to produce a rubber composition, the function of this cellulose (particularly its function as a filler in the rubber composition) is not fully exhibited.

[0006] In addition, rubber compositions used in the manufacture of tires for construction vehicles and the like are often required to be less prone to heat generation (low heat generation) and to have both excellent wear resistance and chipping resistance, but if a masterbatch in which the cellulose is not uniformly dispersed is used in the manufacture of such a rubber composition, it is difficult to obtain a rubber composition that is less prone to heat generation and has both excellent wear resistance and chipping resistance. It is even more difficult to directly mix cellulose with the rubber components in the manufacture of a rubber composition and uniformly disperse it without using a masterbatch in which cellulose is dispersed.

[0007] Therefore, an object of the present invention is to provide a cellulose-containing rubber composition which is less prone to heat generation and has excellent abrasion resistance and chipping resistance. [Means for solving the problem]

[0008] In order to solve the above problems, the present inventors have conducted extensive research and have found that a rubber composition which is formulated with a diene rubber, an inorganic filler, a cellulose-containing masterbatch, and a mixture of a fatty acid and a resin acid, where the cellulose-containing masterbatch contains a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, and which contains 30 to 100 parts by mass of an inorganic filler, 0.5 to 10 parts by mass of cellulose, and a total of 0.2 to 8 parts by mass of the mixture of a fatty acid and a resin acid per 100 parts by mass of the diene rubber, is resistant to heat generation and has excellent abrasion resistance and chipping resistance, thereby completing the present invention.

[0009] That is, the present invention provides the following <1> ~ <6> It is. <1> A rubber composition containing a diene rubber, an inorganic filler, a cellulose-containing masterbatch, and a mixture of a fatty acid and a resin acid, wherein the cellulose-containing masterbatch contains a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid, and the rubber composition contains 30 to 100 parts by mass of the inorganic filler, 0.5 to 10 parts by mass of the cellulose, and a total of 0.2 to 8 parts by mass of the mixture of the fatty acid and the resin acid per 100 parts by mass of the diene rubber. <2> The cellulose is powdered cellulose. <1> The rubber composition according to claim 1. <3> The cellulose is cellulose nanofibers and / or cellulose nanocrystals; <1> The rubber composition according to claim 1. <4> The mixture of fatty acids and resin acids is crude tall oil. <1> ~ <3> The rubber composition according to any one of the above. <5> The mixture of fatty acid and resin acid has a mass ratio of resin acid to fatty acid (resin acid / fatty acid) of 0.9 or more. <1> ~ <4> The rubber composition according to any one of the above. <6> <1> ~ <5> A tire using the rubber composition according to any one of claims 1 to 5. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a cellulose-containing rubber composition which is resistant to heat generation and has excellent abrasion resistance and chipping resistance. [Brief description of the drawings]

[0011] [Figure 1] 1 is a partial cross-sectional schematic view of a tire showing an example of an embodiment of a tire of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described. The present invention relates to a rubber composition containing a diene rubber, an inorganic filler, a cellulose-containing masterbatch, and a mixture of a fatty acid and a resin acid, the cellulose-containing masterbatch containing a diene rubber, a cellulose, and a mixture of a fatty acid and a resin acid, and a rubber composition containing 30 to 100 parts by mass of an inorganic filler, 0.5 to 10 parts by mass of cellulose, and a total of 0.2 to 8 parts by mass of the mixture of a fatty acid and a resin acid per 100 parts by mass of the diene rubber, and a tire using the rubber composition. Hereinafter, these are also referred to as the "rubber composition of the present invention" and the "tire of the present invention".

[0013] In the present invention, unless otherwise specified, a numerical range expressed using "~" means a numerical range having the numerical value before "~" as the lower limit and the numerical value after "~" as the upper limit.

[0014] The components and materials contained in the rubber composition of the present invention, their contents, etc. will be described in detail below.

[0015] [Diene rubber] The diene rubber compounded in the rubber composition of the present invention is a rubber component having a double bond in the polymer main chain, and specific examples thereof include natural rubber (NR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), acrylonitrile-butadiene copolymer rubber (NBR), chloroprene rubber (CR), synthetic isoprene rubber (IR), etc. Such diene rubbers can be used alone or in combination of two or more kinds.

[0016] In particular, in the rubber composition of the present invention, it is preferable that the diene rubber contains NR and / or IR. In particular, from the viewpoint of use in construction vehicle tires, it is more preferable that the diene rubber contains NR and / or IR in total preferably 60 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, and even more preferably 90 mass% or more, and may be a diene rubber consisting of NR and / or IR. It is particularly preferable that the diene rubber consists of NR.

[0017] The weight average molecular weight of each of these diene rubbers is preferably 50,000 to 3,000,000, and more preferably 100,000 to 2,000,000. Furthermore, each of these may be graft-modified with a vinyl monomer or epoxidized with an organic peracid. In the present invention, the "weight average molecular weight" refers to a value measured in terms of standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent. The GPC measurement is performed at 40°C using a column (MIXED-B, manufactured by Polymer Laboratories) as a measuring instrument.

[0018] The rubber composition of the present invention may contain rubber components other than diene-based rubber, but it is preferable that 90% by mass or more of the rubber components contained are diene-based rubber, more preferably 95% by mass or more are diene-based rubber, and even more preferably the rubber components contained are made of diene-based rubber (100% by mass of diene-based rubber).

[0019] [Cellulose-containing masterbatch] The cellulose-containing masterbatch to be blended in the rubber composition of the present invention contains a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid. These will be described in detail below.

[0020] <Cellulose-containing masterbatch diene rubber> The diene rubber contained in the cellulose-containing masterbatch is not particularly limited as long as it can be made into a rubber latex (a water dispersion in which a rubber component is dispersed in a colloidal state in water). For example, a latex of natural rubber (NR), a latex of styrene-butadiene copolymer rubber (SBR), a latex of acrylonitrile-butadiene copolymer rubber (NBR), a latex of chloroprene rubber (CR), etc. can be used. In particular, from the viewpoint of use in construction vehicle tires, it is more preferable to use natural rubber (NR) as the diene rubber. That is, it is more preferable that the diene rubber contained in the cellulose-containing masterbatch contains natural rubber (NR) as a main component, and it is even more preferable that it is made of natural rubber (NR). In addition, this "main component" means that it is contained in 80 mass% or more of the total mass of the diene rubber contained in the cellulose-containing masterbatch, and this ratio is more preferably 90 mass% or more. In addition, the weight average molecular weight of this diene rubber may be the same as that described above. It is preferable to compound this cellulose-containing masterbatch so that the ratio of the diene rubber derived from the cellulose-containing masterbatch to the total amount of diene rubber contained in the rubber composition of the present invention is 20 to 50 mass%, and more preferably 25 to 40 mass%.

[0021] <Cellulose in cellulose-containing master batch> The cellulose contained in the cellulose-containing masterbatch may be, for example, powdered cellulose. This allows a relatively inexpensive cellulose-containing masterbatch to be produced. Here, this powdered cellulose does not include nanocellulose powder (e.g., cellulose nanocrystal powder, etc.) described below. Examples of this powdered cellulose include Viscopal (a product of Rengo Co., Ltd.) as a roughly spherical (uncontrolled shape) powdered cellulose, and KC Flock (a product of Nippon Paper Industries Co., Ltd.) as a fibrous powdered cellulose, but are not limited thereto. The average particle diameter of this powdered cellulose (D 50 ) is not limited, but is preferably 1000 μm or less, more preferably 800 μm or less, even more preferably 600 μm or less, even more preferably 400 μm or less, even more preferably 250 μm or less, and even more preferably 100 μm or less. The lower limit may be 5 μm or more, and may further be 10 μm or more. Here, this "average particle diameter (D 50 "The volume-based average particle diameter (50% volume cumulative distribution diameter (D 50 )).

[0022] The cellulose contained in the cellulose-containing masterbatch is preferably cellulose nanofiber and / or cellulose nanocrystal. This is because the cellulose-containing masterbatch containing these homogeneously dispersed is particularly likely to improve the abrasion resistance and chipping resistance of the rubber composition of the present invention. These are collectively called "nanocellulose", and nanocellulose containing amorphous particles having an average fiber diameter of 1 to 1000 nm and an average fiber length of 0.5 to 5 μm is cellulose nanofiber (CNF, for example, Cellenpia manufactured by Nippon Paper Industries Co., Ltd.), which is also called microfibrillated cellulose. In addition, crystalline (for example, needle-shaped crystals or spherical crystals) nanocellulose having an average fiber diameter of 1 to 1000 nm and an average fiber length of 0.1 to 0.5 μm is cellulose nanocrystal (CNC, for example, Cellulose Nanocrystal manufactured by Fillerbank Co., Ltd.).

[0023] As described above, the average fiber diameter of the cellulose nanofibers and cellulose nanocrystals is 1 to 1000 nm, but it is preferably 1 to 200 nm. The average aspect ratio (average fiber length / average fiber diameter) is preferably 10 to 1000, more preferably 50 to 500. If the average fiber diameter is less than the above range and / or the average aspect ratio exceeds the above range, the dispersibility tends to decrease. If the average fiber diameter exceeds the above range and / or the average aspect ratio is less than the above range, the reinforcing performance tends to decrease.

[0024] Here, the "average fiber diameter" and "average fiber length" refer to the average fiber diameter and fiber length values ​​obtained by obtaining an electron microscope image by TEM or SEM observation at a magnification appropriately set according to the size of the constituent fibers, and measuring at least 50 or more fibers in the image. The average aspect ratio is calculated from the average fiber length and average fiber diameter thus obtained.

[0025] In addition, these celluloses (cellulose as a raw material in the case of nanocellulose) may be derived from wood or non-wood (bacteria, algae, cotton, etc.), and are not particularly limited. In addition, examples of the above-mentioned method for producing nanocellulose include a method in which water is added to the raw cellulose, processed with a mixer, etc. to prepare a slurry in which cellulose is dispersed in water, and this is directly defibrated by applying mechanical shear force using a high-pressure or ultrasonic device, and a method in which this slurry is subjected to chemical treatment such as oxidation treatment, alkali treatment, acid hydrolysis, etc. to modify the cellulose to make it easier to defibrate, and then defibrated by applying mechanical shear force using a disperser, etc. By performing such chemical treatment before defibration, the cellulose can be defibrated more finely and uniformly with low energy, and chemically modified nanocellulose (chemically modified nanocellulose) can be easily obtained. Examples of chemical treatments include treatments with chemical treating agents such as 2,2,6,6-tetramethylpiperidine-1-oxyl (hereinafter referred to as "TEMPO"), 4-acetamido-TEMPO, 4-carboxy-TEMPO, 4-amino-TEMPO, 4-hydroxy-TEMPO, 4-phosphonooxy-TEMPO, phosphoric esters, periodic acid, alkali metal hydroxides, and carbon disulfide. Chemical treatments may also be performed after mechanical defibration of cellulose. In addition to the above-mentioned chemical treatments, cellulase treatment, carboxymethylation, esterification, and treatment with cationic polymers may also be performed after the defibration process.

[0026] The cellulose-containing master batch is produced by mixing such cellulose with the latex of diene rubber. In the rubber composition of the present invention, the cellulose-containing master batch is prepared and blended so that the cellulose derived from the cellulose-containing master batch is contained in an amount of 0.5 to 10 parts by mass per 100 parts by mass of the total of the diene rubber (the total of the diene rubber blended in the rubber composition and the diene rubber solid content derived from the cellulose-containing master batch). From the viewpoint of dispersibility of cellulose, the upper limit is more preferably 8 parts by mass or less, more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less. From the viewpoint of physical properties when vulcanized rubber, the lower limit is more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more.

[0027] The cellulose is preferably contained in an amount of 1 to 20 parts by mass per 100 parts by mass of diene rubber contained in the cellulose-containing masterbatch (100 parts by mass of solids in diene rubber latex), since this is easy to keep within the above range. The upper limit is more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less. The lower limit is more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more.

[0028] <Mixture of fatty acid and resin acid in cellulose-containing masterbatch> The mixture of fatty acid and resin acid contained in this cellulose-containing masterbatch is a component for dispersing cellulose homogeneously, and is not limited as long as both fatty acid and resin acid are contained and the total amount of these is more than 50 mass% (preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more), and components such as unsaponifiable matter may be further contained. Crude tall oil is a preferred example of such a mixture of fatty acid and resin acid. Here, this "crude tall oil" is a by-product recovered in the Kraft process in which chemicals such as sodium hydroxide are added to wood chips and decomposed (alkali decomposition) under high temperature and high pressure to extract pulp fibers, and can be obtained by neutralizing black liquor, which is a concentrated liquid containing lignin that solidified the pulp fibers, resin components, and chemicals, with an acid such as sulfuric acid. Note that tall rosin and tall oil fatty acid are obtained by rectifying this crude tall oil, and distilled tall oil is recovered as a by-product when these are separated. The type of wood that is the raw material for crude tall oil is not particularly limited, but it is preferable that it is crude tall oil derived from pine. The type of pine is not particularly limited, and examples include horse-ear pine, Tudor pine, Elliotti pine, etc. However, for example, a raw material containing a fatty acid and a raw material containing a resin acid may be prepared separately and then mixed for use. The rubber composition of the present invention is constituted such that a mixture of fatty acid and resin acid is blended in a predetermined composition as described below, and the rubber composition contains a cellulose-containing master batch containing the mixture of fatty acid and resin acid, so that the function of cellulose as a filler in the rubber composition is fully exerted. Note that it is important that this is a mixture of fatty acid and resin acid, and the effect of the present invention is not fully exerted by using only resin acid or resin acid alone.

[0029] In addition, because this makes it easier to increase the dispersibility of cellulose, it is more preferable for the fatty acid to be a mixture containing oleic acid and / or linoleic acid, and even more preferable for the mixture to be a mixture containing both oleic acid and linoleic acid and containing more oleic acid than linoleic acid. For the same reason, it is more preferable that the resin acid is a mixture containing one or more selected from the group consisting of abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, and dehydroabietic acid, and it is even more preferable that the resin acid is a mixture containing one or more selected from the group consisting of abietic acid, neoabietic acid, and palustric acid.

[0030] In particular, since the effects of the present invention are more easily achieved, it is more preferable that this mixture of fatty acid and resin acid is a mixture in which the mass ratio of resin acid to fatty acid (resin acid / fatty acid) is 0.9 or more, and it is even more preferable that the mixture is crude tall oil in which this mass ratio is 0.9 or more. The lower limit is more preferably 1.0 or more, and even more preferably 1.1 or more, and the upper limit is more preferably 2.0 or less, and even more preferably 1.8 or less, and even more preferably 1.5 or less.

[0031] The cellulose-containing masterbatch may contain other components than those described above, provided that the effects of the present invention are not affected. In addition, the cellulose-containing masterbatch may contain inorganic fillers, which will be described later, and in this case, the amount of the inorganic fillers contained in the rubber composition of the present invention is within the range described later. Alternatively, the cellulose-containing masterbatch may be made of a mixture of a diene rubber, cellulose, and a fatty acid and a resin acid. An example of a method for producing the cellulose-containing masterbatch is described below. First, cellulose is added to the rubber latex of diene rubber, and a mixture of fatty acid and resin acid is further added. If necessary, other components are further added to obtain a raw material dispersion in a slurry state with a solid content concentration of 60% by mass or less. The dispersion method is not particularly limited, and may be performed by a mechanical method or the like. When using the above-mentioned nanocellulose, it may be made into an aqueous dispersion of nanocellulose and then mixed with the rubber latex. Then, while stirring the obtained raw material dispersion, a coagulant (such as an inorganic salt) is added to coagulate the polymer component, and the coagulated product and water are roughly separated by filtration or the like, and the coagulated product is washed to remove the coagulant as necessary, and further, if necessary, a drying treatment of the coagulated product (for example, a treatment of drying under conditions of 50 to 100 ° C for 0.5 to 30 hours) or the like is performed to obtain a cellulose-containing masterbatch.

[0032] [Mixture of fatty acids and resin acids] The rubber composition of the present invention further contains a mixture of fatty acid and resin acid in addition to the mixture of fatty acid and resin acid contained in the cellulose-containing masterbatch. The mixture of fatty acid and resin acid contained in the rubber composition of the present invention can be the same as the mixture of fatty acid and resin acid contained in the cellulose-containing masterbatch. The rubber composition of the present invention contains 0.2 to 8 parts by mass of the mixture of fatty acid and resin acid and the mixture of fatty acid and resin acid derived from the cellulose-containing masterbatch in total per 100 parts by mass of the diene rubber (the total of the diene rubber solid content derived from the diene rubber and the diene rubber compounded in the rubber composition). The upper limit is more preferably 7.5 parts by mass or less from the viewpoint of physical properties when vulcanized rubber is obtained. From the viewpoint of the dispersibility of cellulose, the lower limit is more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, even more preferably 2.5 parts by mass or more, even more preferably 3.5 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more.

[0033] Furthermore, the mixture of fatty acid and resin acid preferably contains 0.4 to 10 parts by mass of the mixture of fatty acid and resin acid blended and the mixture of fatty acid and resin acid derived from the cellulose-containing master batch per 1 part by mass of cellulose. The upper limit is more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less. The lower limit is more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more.

[0034] [Inorganic filler] The inorganic filler to be compounded in the rubber composition of the present invention is not particularly limited, and examples thereof include carbon black, silica, clay, calcium carbonate, magnesium carbonate, mica, talc, alumina, aluminum hydroxide, titanium oxide, calcium sulfate, barium sulfate, etc., and one of these may be used alone or two or more may be used in combination. In particular, the rubber composition of the present invention preferably contains carbon black and / or silica as the inorganic filler, and more preferably contains carbon black. The term "carbon black" refers to fine carbon particles made of primary particles with a diameter of about 3 to 500 nm that are industrially produced under quality control. The term "silica" refers to silicon dioxide (SiO 2 ) or contains silicon dioxide as a main component (e.g., contains 80% by mass or more, or even 90% by mass or more).

[0035] The carbon black is not particularly limited, and any known carbon black used in applications such as tires can be used. For example, specific examples of carbon black that can be used include various grades such as SAF-HS, SAF, ISAF-HS, ISAF, ISAF-LS, IISAF-HS, HAF-HS, HAF, HAF-LS, FEF, GPF, SRF, FT, and MT. One type of carbon black may be used alone, or two or more types may be used in combination. The nitrogen adsorption specific surface area (N 2SA) is 70 to 145 mm, especially from the viewpoint of use in construction vehicle tires. 2 / g, and 85 to 130m 2 It is more preferable that the nitrogen adsorption specific surface area (N 2 SA) is 145m 2 If it exceeds 1 / g, it tends to become difficult to maintain the low heat build-up property of the rubber composition. The nitrogen adsorption specific surface area (N 2 Specific surface area (SA) is the amount of nitrogen adsorbed onto the surface of carbon black, measured according to JIS K6217-2:2001 "Part 2: Determination of specific surface area - Nitrogen adsorption method - Single point method."

[0036] The silica is also not particularly limited, and any known silica that is blended in rubber compositions for use in tires, etc. Specific examples include wet silica, dry silica, fumed silica, diatomaceous earth, etc., and such silicas can be used alone or in combination of two or more kinds.

[0037] The rubber composition of the present invention contains the inorganic filler as described above, and contains 30 to 100 parts by mass of the inorganic filler relative to 100 parts by mass of the diene rubber. When the cellulose-containing master batch contains an inorganic filler, the total amount including the amount of the inorganic filler is within the above range. Furthermore, this amount is more preferably 35 parts by mass or more relative to 100 parts by mass of the diene rubber. It is more preferably 90 parts by mass or less, more preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less. If this amount is less than 30 parts by mass relative to 100 parts by mass of the diene rubber, the wear resistance and chipping resistance of the rubber composition are not sufficient. If this amount exceeds 100 parts by mass relative to 100 parts by mass of the diene rubber, the low heat generation property of the rubber composition cannot be maintained.

[0038] [Other ingredients] The rubber composition of the present invention may further contain various additives that are generally used in rubber compositions, such as organic fillers (organic fillers, for example, lecithin) other than those described above, resin components, process oils, waxes, zinc oxide (zinc white), stearic acid, antioxidants, plasticizers, curing agents, silane coupling agents, vulcanizing agents (for example, sulfur), vulcanization accelerators, and vulcanization acceleration aids, within the range that does not significantly affect the effects of the present invention, and these additives can be kneaded by a known method to form a rubber composition. However, the rubber composition of the present invention does not contain any material containing cellulose other than the cellulose-containing masterbatch. In other words, the rubber composition of the present invention does not substantially contain any cellulose other than the cellulose derived from the cellulose-containing masterbatch. Here, "substantially not contained" means that the content is less than 0.1 mass%.

[0039] For example, the content of the process oil in the rubber composition of the present invention is preferably 1 to 10 parts by mass, more preferably 2 to 8 parts by mass, based on 100 parts by mass of the total of the diene rubbers. This allows the hardness of the rubber composition of the present invention to be adjusted, and the processability of the rubber composition to be improved. The content of each of the stearic acid, zinc oxide, and antioxidant in the rubber composition of the present invention is preferably 1 to 5 parts by mass based on 100 parts by mass of the total of the diene rubbers. The content of the vulcanizing agent in the rubber composition of the present invention is preferably 0.3 to 3.0 parts by mass, more preferably 0.5 to 2.5 parts by mass, based on 100 parts by mass of the diene rubber in total. The content of the vulcanization accelerator in the rubber composition of the present invention is preferably 0.3 to 3.0 parts by mass, more preferably 0.5 to 2.0 parts by mass, based on 100 parts by mass of the diene rubber in total, either as a primary accelerator alone or as a blend with a secondary accelerator.

[0040] [Manufacturing method etc.] The method for producing the rubber composition of the present invention may be a conventional method and is not particularly limited. As an example of the production method, the diene rubber, the inorganic filler, the predetermined cellulose-containing master batch, the mixture of the fatty acid and the resin acid, and other components as necessary are kneaded and mixed at room temperature or at a high temperature using a kneading machine such as a Banbury mixer, a kneader, or a roll, to produce the rubber composition of the present invention. When using a vulcanization-based component (sulfur, a vulcanization accelerator, a vulcanization accelerator assistant, etc.), it is preferable to first mix the other components at a high temperature, cool the mixture, and then mix the vulcanization-based component.

[0041] The rubber composition of the present invention obtained as described above is a cellulose-containing rubber composition which is resistant to heat generation and has excellent abrasion resistance and chipping resistance.

[0042] The tire of the present invention, which is resistant to heat generation and has excellent abrasion resistance and chipping resistance, can be obtained by using the rubber composition for tires of the present invention. The tire of the present invention is preferably a pneumatic tire, and the gas to be filled in the pneumatic tire can be, for example, air, inert gas such as nitrogen, argon, helium, or other gas.

[0043] In particular, by using the rubber composition of the present invention at least in the cap tread portion (e.g., the portion indicated by reference numeral 3 in FIG. 1) that comes into contact with the road surface of the tire and / or the sidewall portion (e.g., the portion indicated by reference numeral 2 in FIG. 1) that constitutes the side surface of the tire, more preferably in the cap tread portion, an excellent tire for construction vehicles can be obtained. The rubber composition of the present invention may be used partially in a portion of the cap tread portion and / or the sidewall portion (e.g., the surface layer thereof). Furthermore, the tire of the present invention may be constructed using the rubber composition of the present invention in members other than these (e.g., the bead portion indicated by reference numeral 1 in FIG. 1), or the entire tire of the present invention (the entire portion constituted by the rubber composition) may be constituted by the rubber composition of the present invention.

[0044] Hereinafter, examples of the present invention will be described, however, the present invention is not limited to the following examples, and various modifications are possible within the technical concept of the present invention. EXAMPLES

[0045] (Preparation and Evaluation of Rubber Compositions) Rubber compositions having the ingredients shown in Table 1 below were prepared.

[0046] Specifically, the components (except for the vulcanization accelerator and sulfur) in the parts by mass shown in the upper part of Table 1 below were mixed for 5 minutes after heating to about 150°C using a 1.7-liter closed Banbury mixer, and then released from the mixer and cooled to room temperature. Furthermore, using the Banbury mixer, predetermined amounts of the vulcanization accelerator and sulfur were mixed and kneaded, and the mixture was press-vulcanized at 170°C for 10 minutes in a predetermined mold to produce the rubber compositions (vulcanized rubber test pieces) of Comparative Examples 1 to 3 and Examples 1 to 2.

[0047] The obtained rubber compositions (vulcanized rubber test pieces) of Comparative Examples 1 to 3 and Examples 1 and 2 were evaluated for heat build-up, abrasion resistance, and chipping resistance as described below.

[0048] <Fever> For each of the obtained vulcanized rubber test pieces, tan δ(60°C) was measured using a viscoelasticity spectrometer manufactured by Toyo Seiki Seisakusho under conditions of initial strain of 10%, amplitude of ±2%, frequency of 20 Hz and temperature of 60°C. The results are shown in the lower part of Table 1 below. The results are expressed as an index with the value of Comparative Example 1 being 100, and the index was converted so that the lower the heat generation property, the higher the index. In other words, the higher the index, the more difficult it is to generate heat.

[0049] <Wear resistance> For each of the obtained vulcanized rubber test pieces, the amount of wear was measured at a temperature of 20° C. and a slip ratio of 50% using a Lambourn abrasion tester (manufactured by Iwamoto Seisakusho Co., Ltd.) in accordance with JIS K6264-1, 2:2005. The results are also shown in the lower part of Table 1. The results are expressed as an index with the value of Comparative Example 1 being 100, and the smaller the amount of wear, the larger the index. In other words, the larger the index, the more excellent the wear resistance.

[0050] <Chipping resistance> For each of the obtained vulcanized rubber test pieces, the crack growth (unit: mm) after 100,000 flex cycles was measured according to the De Mattia flex crack growth test of JIS K6260, with a stroke of 57 mm, a speed of 300±10 rpm, and a bending speed of 100,000 cycles. The results are also shown in the lower part of Table 1. The results are expressed as an index with the value of Comparative Example 1 being 100. In other words, a larger index indicates better chipping resistance.

[0051] [Table 1]

[0052] The details of each component in Table 1 above are as follows: NR: Natural rubber (TSR20, glass transition temperature (Tg): -62°C) Cellulose-containing masterbatch 1: 30 parts by mass of natural rubber latex (NR: HYTEX HA, high ammonia type, solid content concentration 60% by mass, manufactured by SIME DARBY PLANTATION SDN BHD) as solid content, and powdered cellulose (Viscopal D-30: average particle diameter (D 50 A cellulose-containing masterbatch obtained by mixing 3 parts by mass of cellulose ether (20 to 40 μm, manufactured by Rengo Co., Ltd.) Cellulose-containing masterbatch 2: Natural rubber latex (NR: HYTEX HA, high ammonia type, solid content concentration 60 mass%, manufactured by SIME DARBY PLANTATION SDN BHD) 30 mass parts as solid content, powdered cellulose (Viscopal D-30: average particle diameter (D 50 A cellulose-containing masterbatch obtained by mixing 3 parts by mass of cellulose acylate 20 to 40 μm, manufactured by Rengo Co., Ltd.) and 1.8 parts by mass of crude tall oil. Cellulose-containing masterbatch 3: A cellulose-containing masterbatch obtained by mixing 30 parts by mass of natural rubber latex (NR: HYTEX HA, high ammonia type, solid content concentration 60% by mass, manufactured by SIME DARBY PLANTATION SDN BHD) as solid content, 3 parts by mass of cellulose nanofiber (oxidized cellulose nanofiber: manufactured by Nippon Paper Industries Co., Ltd., Cellenpia), and 1.8 parts by mass of crude tall oil. *The crude tall oil (pine-derived crude tall oil) used in cellulose-containing masterbatches 2 and 3 contains a total of 80% or more by mass of fatty acids and resin acids, the mass ratio of resin acids to fatty acids (resin acid / fatty acid) is approximately 1.2, and of the fatty acids contained, approximately 50% is oleic acid and approximately 35% is linoleic acid, and the resin acids include at least abietic acid, neoabietic acid, and palustric acid. Carbon black: Show Black N339 (Nitrogen adsorption specific surface area (N 2 SA):88m 2 / g, manufactured by Gabot Japan Co., Ltd.) Process oil: Extract No. 4S (Shell Lubricants Japan) Crude tall oil: The same as that used in cellulose-containing masterbatches 2 and 3 Stearic acid: Stearic acid YR (NOF Corporation) Zinc oxide: Zinc oxide (ZnO, manufactured by Seido Chemical Industry Co., Ltd.) Anti-aging agent: Ozonone 6C (Seiko Chemical Co., Ltd.) Vulcanization accelerator: Noccela NS-P (Ouchi Shinko Chemical Industry Co., Ltd.) Sulfur: Myucron OT-20 (manufactured by Shikoku Chemical Industry Co., Ltd.)

[0053] From these results, it was shown that in a rubber composition containing natural rubber, carbon black, crude tall oil, and a cellulose-containing masterbatch containing crude tall oil, by configuring the composition to contain 40 parts by mass of carbon black, 3 parts by mass of cellulose, and a total of 7.2 parts by mass of crude tall oil per 100 parts by mass of natural rubber (including the total of natural rubber contained in the cellulose-containing masterbatch) (Examples 1-2), a rubber composition that is difficult to heat up and has excellent abrasion resistance and chipping resistance was obtained. These were recognized to be rubber compositions particularly suitable for use in the cap tread and sidewall parts of tires for construction vehicles. On the other hand, when the blending amount of cellulose was outside the range, heat generation was likely to occur and neither wear resistance nor chipping resistance was improved (Comparative Example 2). In addition, the rubber composition prepared without separately blending crude tall oil was likely to generate heat (Comparative Example 3). [Explanation of symbols]

[0054] 1 Bead section 2 Sidewall 3 Cap tread section 4 Carcass layer 5 Bead Core 6 Bead Filler 7 Belt layer 8 Rim cushion

Claims

1. A rubber composition containing a diene rubber, an inorganic filler, a cellulose-containing master batch, and a mixture of a fatty acid and a resin acid, the cellulose-containing masterbatch comprises a diene rubber, cellulose, and a mixture of a fatty acid and a resin acid; The rubber composition contains 30 to 100 parts by mass of the inorganic filler, 0.5 to 10 parts by mass of the cellulose, and 0.2 to 8 parts by mass of the mixture of the fatty acid and the resin acid relative to a total of 100 parts by mass of the diene rubber.

2. The rubber composition of claim 1 , wherein the cellulose is powdered cellulose.

3. The rubber composition according to claim 1 , wherein the cellulose is a cellulose nanofiber and / or a cellulose nanocrystal.

4. The rubber composition according to any one of claims 1 to 3, wherein the mixture of fatty acid and resin acid is crude tall oil.

5. The rubber composition according to any one of claims 1 to 3, wherein the mixture of fatty acid and resin acid has a mass ratio of resin acid to fatty acid (resin acid / fatty acid) of 0.9 or more.

6. A tire using the rubber composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Rubber composition

    JP2017095611A